(untitled) (Journal Of Educational and Psychological Researches, 2022)
The objective of the research is to identify the level of supervisory performance of the educational supervisor from the point of view of headmasters at secondary schools. The problem was the need to evaluate performance. A sample of (97) school headmasters was chosen to collect the needed data, they proportionated (38%) of the total community. the researcher designed a questionnaire consisted of (43) paragraphs with five areas. The results showed that there is a good level of performance among supervisors; there are no significant differences in the variable of the certificate, while there were significant differences in terms of gender for the benefit of males. The research concluded with a number of recommendations and suggestions.